Adsorption of metsulfuron-methyl on soils under no-till system in semiarid Pampean Region, Argentina - Zanini, Graciela Pilar (2009)
Adsorption isotherms of metsulfuron-methyl (MM) on thirty soils from the semiarid Pampean Region of Argentina were determined. The effect of total organic carbon (TOC) content on the adsorption was the main focus, but the effects of clay content, specific surface area and pH were also analyzed. pH is a very important factor that affects the adsorption. In fact, this article demonstrates that a good pH control is necessary to investigate the effects of TOC, otherwise results are obscured by changes in pH. Under pH controlled conditions (pH 6.0 ± 0.2), a significant and positive correlation between MM adsorption and TOC was observed for a large range of concentrations (up to 40 mg L- 1). There was no significant correlation between adsorption and inorganic components or specific surface area. The potential mobility of MM in soils was estimated by calculating the groundwater ubiquity score (GUS), using KOC values calculated from adsorption isotherms and appropriate half-times. MM can be ranked as leacher in all the studied soils. The results suggest that MM would be rather mobile and transported by water flows.